PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI P2PNFI REGIONAL II SEMARANG DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI - Sri Rejeki, 11.42.02.0009 (Students Journal of Accounting and Banking, 2013)
This research used the research object at the employees of P2PNFI Regional II Semarang. Every organization should have a disire to reach the optimal result of the work, in this case it needs to increase the organizational commitment, because it influences the competency of employees. Further more, Organization needs to develop the compentence of the employees by training and also increasing the quality of the work environment, because both variables are important to reach the output of the employees.This research is aimed to analize the influence of training to organizational commitment, analize the influence of the work environment to organizational commitment, analize the influence of training to output, analize the influence of the work environment to output, analize the influence of organizational commitment to the competency of employees in P2PNFI Regional two Semarang, This research is an explanatory survey research. The reseach sampling is 115 respondents with the technical census, they are all of the employees of P2PNFI Regional II Semarang. The data analysis technic used is descriptive analysis, intrument analysisÂ (Validity and Reliability), Model test (regression,Â F Test, Adjusted R Square ), T Test ) and mediation efect test. The partialy test result, itâs found a positive and significant influence of training to organizational commitment, the work environment to organizational commitment, training to competency of employees, the work environment to competency of employees, organizational commitment to the competency of employees. The result of mediation indicated thatÂ organizational commitment does not mediate the influence of training and work environment to the competency of employees. The total count of the reseach known that the influence of training is more significan than the influence of work environment to the competency of employees. Â Keyword:Â Â Â Â Â Â Â Training, work environment, organizational commitment and competency of employees.